Persuasive Strategy on UMKM Beverage Advertising in Makassar City and their Implications on Indonesian Language Learning - Arianto Gunawan; Azis Azis; Munirah Munirah (Universitas Cokroaminoto Palopo, 2022)
This study aims to (1) describe the persuasive strategies used in UMKM beverage advertisements in Makassar City, and (2) describe the form of persuasive discourse implications used in UMKM beverage advertisements in Makassar City on Indonesian Language Learning in Class VIII. This type of research uses a qualitative descriptive analysis method. with data collection techniques in the form of documentation, interviews, and questionnaires. The data used in this study are divided into two types, namely primary data sources from interviews and questionnaires from Indonesian language teachers in Makassar City, and secondary data in the form of persuasive discourse contained in UMKM beverage advertisements in Makassar City. The results show that (1) the persuasive strategy in terms of rationalization in UMKM beverage advertisements in Makassar City displays reviews that state the truth or facts to readers about the freshness of beverage products sold by prioritizing low prices to consumers. Furthermore, the persuasive strategy in terms of the element of suggestion in UMKM beverage advertisements in Makassar City displays praiseworthy reviews with the use of sweetener sentences in luring readers to buy the beverage products being sold. And, a persuasive strategy in terms of identification elements in UMKM beverage advertisements in Makassar City displays reviews that prioritize the tastes, desires, and trends that occur in the community by processing appropriate advertising discourse in attracting readers' sympathizers to buy beverage products being sold. (2) The persuasive discourse of UMKM beverage advertisements in Makassar City on learning has a relationship with its use as teaching material in advertising text learning in class VIII which can educate students about local advertising in Makassar City.